Does Agglomeration Matter Everywhere?: New Firm Location Decisions in Rural and Urban Markets - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F. (Journal of Regional Science, 2016)
We test whether commonly used measures of agglomeration economies encourage new firm entry in both urban and rural markets. Using new firm location decisions in Iowa and North Carolina, we find that measured agglomeration economies increase the probability of new firm entry in both urban and rural areas. Firms are more likely to locate in markets with an existing cluster of firms in the same industry, with greater concentrations of upstream suppliers or downstream customers, and with a larger proportion of college-educated workers in the local labor supply. Firms are less likely to enter markets with no incumbent firms in the sector or where production is concentrated in relatively few sectors. The same factors encourage both stand-alone start-ups and establishments built by multiplant firms. Commuting decisions exhibit the same pattern as new firm entry with workers commuting from low to high agglomeration markets. Because agglomeration economies are important for rural firm entry also, policies encouraging new firm entry should focus on relatively few job centers rather than encouraging new firm entry in every small town.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jors.12202
Keywords: dept.eco

U.S. Macroeconomic News and International Stock Prices: Evidence from Newspaper Coverage - Birz, Gene; Dutta, Sandip (Accounting and Finance Research, 2016)
Existing studies provide mixed evidence that the U.S. macroeconomic news impacts international stock prices. We believe this may be related to the fact that economic surprises may not capture how investors interpret macroeconomic releases in various economic conditions. Consequently, we follow Birz and Lott (2011) and use newspaper coverage of economic releases as a measure of news. We argue that in addition to capturing the surprise component of macroeconomic releases, newspaper coverage provide interpretation of these releases similarly to how investors may interpret them in various economic conditions. Out of 15 examined international stock markets, we find that the U.S. macroeconomic news impacts stock returns of 12 countries.
Keywords: dept.eco

MADness in the method: On the volatility and irregularity of technology diffusion - Bodo, Peter (Technological Forecasting and Social Change, 2016)
The paper investigates how some drivers of technology diffusion shape the volatility and irregularity of the diffusion process. It presents an agent-based simulation model of technology diffusion that includes variables to control technology generations, social pressures, market size, and network randomness. Several variable combinations are defined, technology diffusions are simulated, and the volatility and irregularity of the process are measured. The paper explores scenarios with unusually high volatility and/or irregularity in more detail. It shows that technology generations mostly affect volatility, social pressures impact irregularity, while network randomness and market size amplify the other two factors' effects. Also, the paper argues that market structure changes generated by the factor combinations in question indirectly affect diffusion volatility and irregularity and these indirect effects may explain very high levels of, and unexpected changes in the volatility and irregularity of the technology diffusion process. (C) 2016 Elsevier Inc All.rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-992-710-626-913 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Agent-based model; Agent-based models; Agent-based simulation models; Autonomous agents; Brand and product category competition; Commerce; Computational methods; Control technologies; Diffusion; Diffusion process; Economic and social effects; Market structures; Network randomness; Product categories; Random processes; Several variables; Technology diffusion; Technology generations; competition (economics); dept.eco; network analysis; numerical model; technology diffusion

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Citation Key Alias: lens.org/145-753-875-477-19X
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Sustainable growth with irreversible stock effects of renewable resources - Lopez, Ramon; Yoon, Sang Won (Economics Letters, 2016)
This paper examines sustainability conditions when the stock effects of renewable resources prevail, and characterizes the maximal critical level of initial pollution emissions such that Pigovian tax alone ensures sustainable growth. (C) 2016 Elsevier B.V. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/081-651-810-246-326 tex.type: [object Object]
Keywords: Optimal pollution tax; Renewable resources; Stock effects; Sustainable growth; dept.eco